1985
DOI: 10.1152/jappl.1985.59.3.710
|View full text |Cite
|
Sign up to set email alerts
|

Delayed onset muscle soreness following repeated bouts of downhill running

Abstract: Perceived muscle soreness ratings, serum creatine kinase (CK) activity, and myoglobin levels were assessed in three groups of subjects following two 30-min exercise bouts of downhill running (-10 degrees slope). The two bouts were separated by 3, 6, and 9 wk for groups 1, 2, and 3, respectively. Criterion measures were obtained pre- and 6, 18, and 42 h postexercise. On bout 1 the three groups reported maximal soreness at 42 h postexercise. Also, relative increases in CK for groups 1, 2, and 3 were 340, 272, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
90
1
2

Year Published

1987
1987
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(107 citation statements)
references
References 0 publications
14
90
1
2
Order By: Relevance
“…The reduction in size of the enzyme response to exercise in the second period of the study has been seen before, both in rats and in humans (Byrnes et al, 1985;Kuipers et al, 1985). This reduction in response cannot be attributed to a M change in aerobic metabolism, since no difference in 72 oxygen consumption was observed between the two downhill runs.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The reduction in size of the enzyme response to exercise in the second period of the study has been seen before, both in rats and in humans (Byrnes et al, 1985;Kuipers et al, 1985). This reduction in response cannot be attributed to a M change in aerobic metabolism, since no difference in 72 oxygen consumption was observed between the two downhill runs.…”
Section: Discussionsupporting
confidence: 65%
“…In this study it is evident that a single bout of 45 minutes downhill running is sufficient to produce a protective effect lasting at least 10 weeks which reduces muscle enzyme release after a second bout of eccentric exercise. Such an effect has been seen up to 6 weeks after an initial downhill run (Byrnes et al, 1985), but a second downhill run at 9 weeks after the first produced the same magnitude of response as the first. The mechanism by which this "repeated bout effect" operates is not yet understood (Byrnes and Clarkson, 1986).…”
Section: Discussionmentioning
confidence: 86%
“…The markers of muscle damage included MVC at 90° of elbow flexion, ROM, CK activity and muscle soreness, which were commonly used as indirect markers of muscle damage in previous studies 5 6 19. All markers were measured 2 days before (pre-exercise) and 1–4 days post-exercise; MVC and ROM were also measured immediately and 1 h post-exercise.…”
Section: Methodsmentioning
confidence: 99%
“…Muscle damage can be assessed via measures of isometric or dynamic strength, range of motion (ROM) about a joint, blood levels of muscle-specific proteins and muscle soreness 35. It has been shown that changes in these markers are influenced by a variety of factors, including exercise intensity,6 7 number of muscle contractions during exercise,8 – 10 exercised muscle length10 11 and exercise performed prior to eccentric exercise 12 13. However, even when such factors are controlled, a large inter-subject variability in the changes in the markers after exercise still exists 14…”
mentioning
confidence: 99%
“…5 When a similar bout is repeated within a few days to six weeks, these markers are significantly lower, suggesting some form of adaptation, a phenomenon referred to as the ''repeated bout effect''. 6 As would be expected in response to exercise induced tissue damage, immune and inflammatory alterations have also been examined, but the focus has been on the innate immune system. 3 7 8 Adaptive immunity is associated with primary and/or secondary immunoglobulin responses to pathogens such as bacteria and viruses.…”
mentioning
confidence: 99%